2012
DOI: 10.1111/emr.12025
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bait uptake by feral cats, Felis catus, in semi‐arid environments

Abstract: Summary Feral cat control using aerial broadcasting of toxic baits continues to be used in the rangelands of Western Australia. The effectiveness of these operations has sometimes been compromised by different environmental factors that affect prey and cat numbers. This study demonstrates that the ratio of cats to their preferred prey (small mammals) can be used to predict the most effective time to bait. The regular baiting of three conservation sites offered an opportunity to study the relationship between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…Roy et al (2002) reported that generic control of mongoose, Herpestes javanicus, failed to prevent uncommon but significant predation events on the rare pink pigeon, Columbus mayeri, in Mauritius and called for studies into the behavioral ecology of the mongoose. Several studies suggest that predation pressure of feral cats may also vary intraspecifically due to their size or prior learning (Childs, 1986;Christensen et al, 2012;Kuo, 1930). Dickman and Newsome (2015) identified specialist predators within several populations of feral cats that achieved maximal hunting success when attacking particular prey.…”
Section: Introductionmentioning
confidence: 99%
“…Roy et al (2002) reported that generic control of mongoose, Herpestes javanicus, failed to prevent uncommon but significant predation events on the rare pink pigeon, Columbus mayeri, in Mauritius and called for studies into the behavioral ecology of the mongoose. Several studies suggest that predation pressure of feral cats may also vary intraspecifically due to their size or prior learning (Childs, 1986;Christensen et al, 2012;Kuo, 1930). Dickman and Newsome (2015) identified specialist predators within several populations of feral cats that achieved maximal hunting success when attacking particular prey.…”
Section: Introductionmentioning
confidence: 99%
“…Although poison baiting can be successful for con trolling feral cats when they are food-stressed (Burrows et al 2003;Johnston et al 2011), this control method has limited efficacy when prey are abundant (Risbey et al 1997;Algar et al 2007;Moseby et al 2009;Christensen et al 2013). Indeed evidence suggests that an increase in cat predation following successful fox baiting may be implicated in subsequent declines in wildlife vulnerable to cat predation (Christensen and Burrows 1995;Risbey et al 2000;Johnson 2006;Read and Ward 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Algar and Burrows (2003) found that cat densities could be reduced by 80-90% from baiting at 100 baits/ km 2 on islands. Christensen et al (2013) repeatedly baited Lorna Glen reserve on the Australian mainland at 50 baits/km 2 , and we use their observations from 2003 and 2004. We solve Eq.…”
Section: Parameter Identificationmentioning
confidence: 99%
“…Here, we consider a situation where the effectiveness of control efforts varies throughout the year. For example, the willingness of feral cats to consume poison baits is inversely related to the seasonal availability of alternative food sources (Algar et al 2007, Christensen et al 2013. Although managers often cope with varying control effectiveness by halting control efforts during periods of low efficacy, this is not necessarily the best response.…”
Section: Seasonally Varying Effectiveness Of Controlmentioning
confidence: 99%